Changes in carotid artery texture by ultrasound and elastin features in a murine model - Mitchell, Carol; Al Mukaddim, Rashid; Liu, Yuming; Graham, Melissa; Eickhoff, Jens C.; Weichmann, Ashley M.; Tattersall, Matthew C.; Korcarz, Claudia E.; Stein, James H.; Varghese, Tomy; Eliceiri, Kevin W. (Frontiers in Cardiovascular Medicine, 2023)
Objective: In humans, arterial grayscale ultrasound texture features independently predict adverse cardiovascular disease (CVD) events and change with medical interventions. We performed this study to examine how grayscale ultrasound texture features and elastin fibers change in plaque-free segments of the arterial wall in a murine model prone to atherosclerosis. Methods: Ten Apoe tm1Unc/J mice (n=5 male, n=5 female) were imaged at 6, 16, and 24 weeks of age. Two mice were euthanized at 6 and 16 weeks and the remaining mice at 24 weeks. Texture features extracted from the ultrasound images of the distal 1.0 mm of the common carotid artery wall and elastin measures were extracted from histology images. Two-way analysis of variance (ANOVA) was used to evaluate associations between week, sex, and grayscale texture features. Texture feature and elastin number comparisons between weeks were conducted using the sex by week two-way interactions contrasts. Sex-specific correlations between the number of elastin fibers and grayscale texture features were analyzed by conducting nonparametric Spearman’s rank correlations analyses. Results: Arterial wall homogeneity changed significantly in male mice from 6 to 24 weeks mean (SD) 0.14 (0.03) units at 6 weeks, and 0.18 (0.03) units at 24 weeks (p=0.026). Spatial gray level dependence matrices-homogeneity (SGLD-HOM) also correlated with carotid artery plaque score (rs = 0.707, p=0.033). Elastin fibers in the region of interest decreased from 6 weeks to 24 weeks for both male and female mice, although only significantly in male mice. The mean (SD) number of elastin fibers for male mice at 6 weeks was 5.32 (1.50), and 3.59 (0.38) at 24 weeks (p=0.023 respectively). For female mice the mean (SD) number of elastin fibers at 6 weeks was 3.98 (0.38), and 3.46 (0.19) at 24 weeks (p=0.051). Conclusion: Grayscale ultrasound texture features that are associated with increased risk for CVD events in humans were used in a murine model and the grayscale texture feature SGLD-HOM was shown to change in male mice from 6 weeks to 24 weeks. Structural alterations of the arterial wall (change in elastin fiber number) were observed during this time and may differ by sex. .